How Whatsapp Changes the Way Business Work? - Terkan, Remziye; Celebi, Serra Inci (International Review of Management and Marketing, 2020)
Using a focus group and a pre-test, this study validates a scale for measuring the motivations, uses and gratifications for WhatsApp, which comprises of dimensions: communication, privacy, credibility, and miscellaneous activities. Workplace WhatsApp usage motivations consists of two dimensions namely, working, planning, & coordination and speed, convenience, & practicality. After the focus group and the pre-test, 455 participants were included in a survey to understand a connection between work performance and WhatsApp usage. The results were discussed in terms of uses and gratifications. Keywords: WhatsApp motivations, work performance, uses and gratifications. JEL Classifications: D83, L25 DOI: https://doi.org/10.32479/irmm.10769